Sustainable Development and Sustainability Management in the European Union Countries - Huttmanová, Emilia (European Journal of Sustainable Development, 2016)
The terms sustainable development and sustainability are now used in many areas and spheres of life and become a modern phenomenon in determining the direction of progress. Sustainability is the goal of many strategic documents and should be implemented in economic and social life. The attractiveness of the terms sustainability and sustainable development leads to high frequency of their use, and is also evidence of their multidisciplinary meaning. The aim of this paper is to evaluate the management of sustainable development in the countries of the European Union through selected indicators characterizing sustainable development and its main dimensions. The paper presents the results of the evaluation of sustainable development using selected methods and indicators. Key words: Sustainability, Management of Sustainability, Sustainable Development, Indicators, Quantification